The problems facing agricultural sector in Zanzibar and the prospects of Waqf-Muzar’ah-Supply Chain Model: the case of clove industry - Moh’d, Issa Salim; Mohamed, Mustafa Omar; Saiti, Buerhan (Emerald, 2017)
Purpose – Since middle of 1960, the clove production has continually and significantly decreased due to some problems and challenges which include financial ones. The financial intermediaries such as banks, cooperatives and micro-enterprises provide micro-financing to the farmers with high interest rates along with collateral requirements. The numerous programmes, measures and policies adopted by the relevant parties to find out the solutions to the dwindling clove production have failed. Therefore, this paper tries to identify the appropriate model to address the financial challenges in agricultural sector in Zanzibar. Design/methodology/approach – We will review and examine several existing financial models and will identify the issues and challenges of the current financial models and will propose an appropriate Islamic financing model. Findings- The numerous programmes, measures and policies adopted by the relevant parties to find out the solutions to the dwindling clove production have failed. This study, therefore, proposed a Waqf-Muzara’ah- Supply Chain model (WMSCM) to address the financial challenge. Partnership arrangement is also suggested in the model to mitigate the issues of high interest rates and collateral that constrains the financial ability of the farmers and their agricultural output. Originality/value - The contribution of the agricultural sector to the economic development of Zanzibar Islands is considerable. As one of the important agricultural sectors, the clove industry was the economic backbone of the government of Zanzibar. This study is believed to be a pioneering work; hence it is the first study that investigates empirically the challenges facing the clove industry in Zanzibar.